Hidden costs of providing care: a pilot study of Japanese migrant care workers’ experiences in Aotearoa New Zealand during the COVID-19 pandemic - Shinya Uekusa (Kōtuitui)
Recognising the increasingly vital yet precarious role that Asian migrant care workers (MCWs) play within Aotearoa New Zealand (Aotearoa) health system, this paper delves into the qualitative exploration of the experiences encountered by Japanese MCWs amidst everyday challenges and injustices during the COVID-19 pandemic in Aotearoa. Gaining in-depth understanding of their lived experiences, encompassing challenges inherent in their care roles and racial/social injustices outside their care roles, holds the potential to establish a sustainable care workforce capable of delivering quality health care while also attracting and retaining MCWs in Aotearoa. Employing the perspective of Critical Migration Studies (CMS), this pilot study explores the hidden costs of care provision, drawing insights from in-depth interviews conducted with 10 Japanese MCWs in late 2022 and early 2023, and presents mixed findings. The data indicates intersecting challenges in their work, including unfair treatment, linguicism, labour market inequality and various forms of social injustices. However, most Japanese MCW participants had developed robust resilience in dealing with these perceived challenges and injustices in Aotearoa, stemming from their previous experiences of gender, cultural and other forms of oppression in their workplace and everyday life in Japan.